Pengaruh ojek dan angkutan umum online terhadap ojek dan angkutan umum konvensional: Studi kasus angkutan ADL dan GRAB di kota Malang - amalia, nur zaibi (Maliki Interdisciplinary Journal, 2025)
Technological advancements have brought significant changes to the transportation sector, especially regarding motorcycle taxis (ojek) and public transport in Malang City. This study aims to analyze the impact of the emergence of online-based motorcycle taxis and public transport services (such as Grab) on the sustainability of conventional motorcycle taxis and public transportation (such as ADL angkot). The research employed a literature review method by collecting data from various literatures, journals, and previous research findings. The results of the study indicate that the emergence of online transportation has caused a decline in the income and number of passengers for conventional motorcycle taxis and public transport. Factors such as ease of access, service features, and fare certainty make online motorcycle taxis more attractive to the public. Conventional motorcycle taxi drivers and public transport drivers have attempted to adapt by strategies such as lowering fares, improving service, and offering charter services for tourism. The Malang City Government has made efforts to improve service quality and fare policies to help conventional transport remain competitive. This study recommends the need for fair regulations and training for conventional drivers to enable them to adapt to technological developments in transportation.